The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3171/2014.9.jns13959
|View full text |Cite
|
Sign up to set email alerts
|

A successful case of multiple stereotactic radiosurgeries for ipsilateral recurrent trigeminal neuralgia

Abstract: Trigeminal neuralgia is a common pain syndrome primarily managed medically, although many patients require surgical or radiotherapeutic intervention. Stereotactic radiosurgery has become a preferred method of treatment given its high efficacy rates and relatively favorable toxicity profile. However, many patients have refractory pain even after repeat courses of stereotactic radiosurgery. Historically, 2 courses have been the limit in such patients. The authors present a case of multiply recurrent trigeminal n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…GKRS has been reported in one small retrospective series, as well as in cases reports. [7][8][9][10] Here, we report the largest series to date of patients who have undergone a third GKRS for repeated treatment failure. Our results showed that a third GKRS is generally an effective treatment, with 18 of 22 cases attaining pain relief (i.e., BNI pain intensity score ≤ IIIb).…”
Section: Figmentioning
confidence: 96%
See 1 more Smart Citation
“…GKRS has been reported in one small retrospective series, as well as in cases reports. [7][8][9][10] Here, we report the largest series to date of patients who have undergone a third GKRS for repeated treatment failure. Our results showed that a third GKRS is generally an effective treatment, with 18 of 22 cases attaining pain relief (i.e., BNI pain intensity score ≤ IIIb).…”
Section: Figmentioning
confidence: 96%
“…5,6 Additional GKRS for multiply recurrent pain is not well described, with the literature limited to case reports and a single retrospective series thus far. [7][8][9][10] In the present retrospective review, we aim to report the outcomes of patients who underwent at least three GKRS procedures to a single trigeminal nerve for medically refractory TN.…”
mentioning
confidence: 99%
“…When pain recurs after three or more years, many GK patients undergo repeat SRS treatment, and numerous series using GK show that the outcome of a second SRS treatment is similar to the initial treatment with 61% excellent or good results within the initial 24 months but with a higher incidence of residual facial numbness [ 34 - 42 ]. There are even case reports of third SRS treatments within the dose restraints of multiple treatments with a debate of the proper dose relative to risk of secondary effects on the adjacent brainstem and the trigeminal nerve and risk of increased facial numbness [ 42 , 43 ]. Although there are numerous reports of series of patients treated with recurrent pain with GK, there are no series reporting the use of CK for recurrent trigeminal neuralgia after initial successful SRS treatment, which is the focus of this report.…”
Section: Introductionmentioning
confidence: 99%